Family still matters: Human social motivation across 42 countries during a global pandemic - PICK, Cari M. (Institutional Knowledge at Singapore Management University, 2022)
The COVID-19 pandemic caused drastic social changes for many, including separation from friends and coworkers, enforced close contact with family, reductions in mobility, and a number of other health-related precautions. Here we assess the extent to which people’s evolutionarilyrelevant basic motivations and goals—their fundamental social motives—might have been affected. To address this question, we gathered data on these motives in 42 countries (N=15,915) in two waves, including 19 countries (N=10,907) for which data were gathered both before and during the pandemic (Pre-pandemic wave: 32 countries, N=8998; 3302 male, 5585 female; Mage=24.43, SD=7.91; Mid-pandemic wave: 29 countries, N=6917; 2249 male, 4218 female; Mage=28.59, SD=11.31). Samples include data collected online (e.g., Prolific, MTurk), at universities, and via community sampling. We found that Disease Avoidance motivation was substantially higher during the pandemic, and that there were small yet significant differences across waves in most of the other fundamental social motives. Most sensibly, concern with caring for one’s children was higher during the pandemic, and concerns with Mate Seeking and Status were lower. Earlier findings showing the prioritization of family motives over mating motives (and even over Disease Avoidance motives) were replicated during the pandemic. Finally, well-being remained positively associated with family motives and negatively associated with mating motives during the pandemic, as it had in the pre-pandemic samples. Our results provide further evidence for the robust primacy of family-related motivations even during this unique disruption of social life